Reflected Spectroscopy of Small Exoplanets. III. Probing the UV Band to Measure Biosignature Gases - Mario Damiano; Renyu Hu; Bertrand Mennesson (The Astronomical Journal, 2023)
Direct-imaging observations of terrestrial exoplanets will enable their atmospheric characterization and habitability assessment. Considering Earth, the key atmospheric signatures for the biosphere are O _2 and the photochemical product O _3 . However, this O _2 –O _3 biosignature is not detectable in the visible wavelengths for most of the time after the emergence of oxygenic photosynthesis life (i.e., Proterozoic Earth). Here we demonstrate spectroscopic observations in the ultraviolet wavelengths for detecting and characterizing O _2 and O _3 in Proterozoic-Earth-like planets, using ExoReL ${}^{{\mathfrak{R}}}$ . For an O _2 mixing ratio 2–3 orders of magnitude less than the present-day Earth and an O _3 mixing ratio of 10 ^−7 to 10 ^−6 , we find that O _3 can be detected and its mixing ratio can be measured precisely (within 1 order of magnitude) in the ultraviolet (0.25–0.4 μ m), in addition to visible-wavelength spectroscopy. With modest spectral resolution ( R = 7) and signal-to-noise ratio (∼10) in the ultraviolet, the O _3 detection is robust against other potential gases absorbing in the ultraviolet (e.g., H _2 S and SO _2 ), as well as the short-wavelength cutoff between 0.2 and 0.25 μ m. While the O _3 detection does not rely on the near-infrared spectra, extending the wavelength coverage to the near-infrared (1–1.8 μ m) would provide essential information to interpret the O _3 biosignature, including the mixing ratio of H _2 O, the cloud pressure, and the determination of the dominant gas of the atmosphere. The ultraviolet and near-infrared capabilities should thus be evaluated as critical components for future missions aiming at imaging and characterizing terrestrial exoplanets, such as the Habitable Worlds Observatory.